Development of a Mobile Application: From University Website to Mobile App - Das, Pranajit Kumar; Paul, Himangshu Shakor; Tultul, Mahadi Hasan (Journal of Ubiquitous Computing and Communication Technologies, 2023)
In the era of technology, people are using smartphones for their everyday needs, like entertainment, communication, and education needs. Various organizations are developing mobile apps for their needs and using them for different purposes. Faculties, students, staff, and other stakeholders of Sylhet Agricultural University expressed surging demand for a mobile app for the university website. In the 21st Century, it was the need of the hour where everyone wanted mobile interactable sites. ICT individuals at the university undertook the mobile app development process and started with a decision that the mobile app should not replicate the full content of the university website. The research analyses the requirements and decide to decorate the app with the basic information such as various statutory bodies, faculty, department, different offices, news, and notice of the university that are necessary for the university stakeholders. Because of data integrity, pieces of information on the app are fetched from the university website automatically using API. As the information updates on the website, the data becomes visible to the app as well, subject to the internet connection. The key feature of this mobile app is that it can use previously saved materials when there is no access to the internet and eventually doesn’t have a chance to access the latest content without internet.